.(proposal Of A Sports Recreational Program To Increase Self-esteem Among Hearing-impaired Adolescents (15-16) Years Old (experimental Study At The School Of Deaf Children In The Town Of Batna For The Academic Year 2016/2017 - cheriet, Houssameddine (sports creativity, 2025)
This study aims to determine the effectiveness of the proposed sports recreational program in raising self-esteem among hearing impaired adolescents (the deaf) (15-16) years. To study the effectiveness, the researcher conducted a field study at the School of Deaf Children located in the center of the midtown of Batna. The study sample included 24 individuals divided according to the sex (12 males and 12 females), and it was chosen by the intentional targeted method of 60% of the research community. The researcher adopted, in this study, the experimental method by conducting a pre-test in January 2017 followed by the application of the recreational program on the sample and then by conducting a post-application in May 2017. The researcher also relied on the scale of Dr. Wahid Mustafa Kamel for self-esteem among the hearing-impaired adolescents as a tool to evaluate self-esteem, and the sports recreational program designed by the researcher and consists of 24 sports recreational classes was applied. The researcher’s findings show that there are differences of statistical significance at the level of 0,01 between the pre and post application in the self-esteem among the hearing impaired adolescents (males and females) in favor of the post-application. The researcher's findings show the effectiveness of the proposed sports recreational program to increase self-esteem among hearing impaired adolescents for both sexes leading us to give great importance to sports recreational activity and adopt it as a means to help hearing impaired people to overcome the difficulties through minimizing the psychological problems experienced by them, as well as paying attention to the hearing-impaired females and highlighting them through conducting studies to find out why they have low self-esteem.